Potential Role of N-Acetylcysteine in the Management of Substance Use Disorders - McClure, Erin A. (2014)
There is a clear and pressing need to expand pharmacotherapy options for substance use disorders (SUDs) in order to improve sustained abstinence outcomes. Preclinical literature has demonstrated the role of glutamate in addiction, suggesting that new targets for pharmacotherapy should focus on the restoration of glutamatergic function. Glutamatergic agents for SUDs may span multiple addictive behaviors and help demonstrate potentially overlapping mechanisms in addiction. The current review will focus specifically on N-acetylcysteine (NAC), a safe and well-tolerated glutamatergic agent, as a promising potential pharmacotherapy for the treatment of SUDs across several substances of abuse. Building on recently published reviews of the clinical efficacy of NAC across a broad range of conditions, this review will more specifically discuss NAC as a pharmacotherapy for SUDs, devoting particular attention to the safety and tolerability profile of NAC, the wealth of preclinical evidence that has demonstrated the role of glutamate dysregulation in addiction, and the limited but growing clinical literature that has assessed the efficacy of NAC across multiple substances of abuse. Preliminary clinical studies show the promise of NAC in terms of safety, tolerability, and potential efficacy for promoting abstinence from cocaine, nicotine, and cannabis. Results from randomized clinical trials have been mixed, but several mechanistic and methodological factors are discussed to refine the use of NAC in promoting abstinence and relapse prevention across several substances of abuse. Further preclinical and clinical investigation into the use of NAC for SUDs will be vital in addressing current deficits in the treatment of SUDs.